Plant Chemistry Determines Host Preference and Performance of an Invasive Insect - Wang, Dingli; Zhou, Lifeng; Wang, Qiyun; Ding, Jianqing (Frontiers in Plant Science, 2020)
Understanding how host plant chemistry affects invasive insects is crucial to determining the physiological mechanism of host use and predicting invasive insect outbreak and damage on hosts. Here, we examined the effects of plant nutrition and defensive chemicals on host preference and performance of adults and larvae of the invasive potato tuberworm, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae), on four native (Solanum tuberosum, Nicotiana tabacum, Datura stramonium and Solanum lycopersicum) and three new (Solanum melongena, Physalis alkekengi, and Lycium barbarum) host plants. We found adults preferred to oviposit on S. tuberosum and N. tabacum leaves and the soil around these native host plants over other hosts. Larvae performed well on S. tuberosum and N. tabacum, reaching higher pupa weight and having better survival. Larvae performed poorly on S. melongena, S. lycopersicum, P. alkekengi, D. stramonium and L. barbarum, with lower pupa weight and lower survival. Solanum tuberosum and N. tabacum had higher leaf soluble proteins than other plants and lower leaf total phenolics than S. lycopersicum, D. stramonium and L. barbarum. Moreover, carbon content and soluble protein were positively associated with larval survival, while defensive traits (lignin and total phenolics) negatively affected larval survival. These findings provide insights into understanding of biochemical mechanisms of interactions between invasive insects and host plants, indicating the importance of considering plant chemistry when assessing invasive insect host use and damage.